(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article examines the current state of legal regulation of road safety in the Kyrgyz Republic. The analysis is carried out within the framework of the current regulatory framework, including laws, by-laws, technical regulations and international obligations of the Kyrgyz Republic. The key problems of legal regulation are identified, manifested in the inconsistency of certain norms with modern requirements, duplication of functions of public authorities, insufficient preventive and law enforcement measures, as well as weak integration of digital control tools. In the course of the identified problems, directions for improving legislation and public administration in the field of road safety are proposed, including a comprehensive modernization of the legal framework, clarifying the competencies of government agencies, the introduction of modern digital systems and strengthening preventive measures. The results of the research can be used in the development of state policy and strategic documents in the field of road safety.